Isoëtes vanensis (Isoëtaceae) sp. nov. from Turkey - Zare, Golshan; Keski̇n, Mustafa; Doğru-Koca, Asli; Armağan, Meti̇n (Phytotaxa, 2016)
A previously undescribed species, Isoëtes vanensis, is described and illustrated. Isoëtes vanensis is distinguished from allied species by its papery scales and small megaspores bearing a low tuberculate texture and a fimbriate-ecuelate micro-ornamentation. A table of comparative diagnostic characters and character states for I. vanensis and allied taxa, a geographic distribution map, and SEM images of megaspores and microspores showing ornamentation patterns are included.